PENGEMBANGAN APLIKASI PERSEDIAAN BARANG BERBASIS WEB MENGGUNAKAN METODE SDLC PADA CV PADU NUSANTARA JAKARTA - Romli; Wiyanto Wiyanto; Sufajar Butsianto (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
CV. Padu Perkasa Nusantara Jakarta is a construction implementation company in the form of CV. Unified MightyArchipelago in Jakarta. So far CV. Padu Perkasa Nusantara Jakarta still using a manual system in carrying out its operationalactivities, especially in processing inventory transaction data that still uses paper stock forms so that the final informationabout the resulting inventory stock sometimes does not match the physical stock in the warehouse. The method used in thisstudy is the Systems Development Life Cycle. This method describes the overall software development process to producequality software and meet the expectations of system users and the programming language used PHP and the MySQL database. The purpose of this research is to develop an inventory system at CV. Padu Perkasa Nusantara Jakarta to facilitate the process of data processing of incoming and outgoing goods and speed up the search for stock and speed up the preparation of inventory reports using the Software Development Life Cycle method.Keywords : Supply, PHP MySQL, Systems Development Life Cycle